THE IMPLEMENTATION OF CHARACTER EDUCATION MODEL BASED ON THEATER EMPOWERMENT - Purwati Anggraini; Tuti Kusniarti (International Conference on Languages and Arts, 2014)
Character education is considered to be important since character is functioned as the power of mental and ethics which encourage the nation to realize the national idea and to show the comparative, competitive, and dynamic excellences among other nations. However, the current implementation of character education is not considered to be successful yet. In addition, character education has been widely implemented in schools so far. The research finding about character education in school shows that the implementations of character education in schools are still mainly based on the school condition and tend to be as what it is (without a good planning). Besides, schools also do not have the character education implementation guideline which is based on school condition and the development of students’ psychology. There are some obstacles of the character education implementation in school, which are human resources, facilities, and lack of support from the family and society. The implementation of character education in elementary school has not involved many parties yet and the evaluation is not done continuously. Since the importance of character education implementation to students, especially for elementary school students, it needs model reconstruction which is appropriate and applicable to elementary school students. Role play is one of the activities in elementary school curriculum which is possibly used as a media to transfer the character value. Besides the fact that role play has not widely introduced yet, it is such a pleasing activity. Role play here is role play which has a concept in the model of theater empowerment. Through this theater empowerment, students will have the experience to involve in the society. Besides, students’ characters can also be forged during the practice session of theater. Therefore, character education model based on theater empowerment can be an alternative of character education in elementary school.   Keywords: Character Education, Theater Empowerment, Elementary School Students